Cultural and social capital : language proficiency and social integration - Lim, Edmund (2018)
Existing literature on migrants’ social integration suggests that it is an ongoing process affected by many aspects. However, language proficiency is an oft-cited variable affecting migrants the most. This can be in tangible terms such as social mobility, work opportunities and wages or in intangible terms such as one’s social networks and integration. Drawing on Bourdeusian capital, this research provides a different look on language proficiency as cultural capital and social integration as social capital. Moving away from contemporary research focusing only on the effects of dominant language (English), the paper first contrasts English with colloquially spoken ‘Singlish’. It diverges further by examining the prominence of an official second language, Mandarin, in Singapore. For multilingual societies like Singapore, Switzerland, Luxembourg and Belgium, this paper illustrates the benefits of official second language’s cultural capital on accumulating social capital for social integration.